Structural characterization of pharmaceutical heparins prepared from different animal tissues. Issue 5 (21st March 2013) - Fu, Li; Li, Guoyun; Yang, Bo; Onishi, Akihiro; Li, Lingyun; Sun, Peilong; Zhang, Fuming; Linhardt, Robert J.
Abstract Although most pharmaceutical heparin used today is obtained from porcine intestine, heparin has historically been prepared from bovine lung and ovine intestine. There is some regulatory concern about establishing the species origin of heparin. This concern began with the outbreak of mad cow disease in the 1990s and was exacerbated during the heparin shortage in the 2000s and the heparin contamination crisis of 2007–2008. Three heparins from porcine, ovine, and bovine were characterized through state‐of‐the‐art carbohydrate analysis methods with a view profiling their physicochemical properties. Differences in molecular weight, monosaccharide and disaccharide composition, oligosaccharide sequence, and antithrombin III‐binding affinity were observed. These data provide some insight into the variability of heparins obtained from these three species and suggest some analytical approaches that may be useful in confirming the species origin of a heparin active pharmaceutical ingredient. © 2013 Wiley Periodicals, Inc. and the American Pharmacists Association J Pharm Sci 102:1447–1457, 2013